27.6k views
25 votes
This is function notation and I have no idea how to do it. I need answers.

This is function notation and I have no idea how to do it. I need answers.-example-1
User Rax Adaam
by
4.3k points

1 Answer

1 vote

Answer:

So you are given the function, f(x) = 3x - 4. You will plug in the value given and solve and write the answer down in the box.

f(x) = 3x - 4 ---> f(5), f(2), f(1), f(10), and f(-1) value given

f(5) = 3(5) - 4

f(5) = 15 - 4

f(5) = 11

f(2) = 3(2) - 4

f(2) = 6 - 4

f(2) = 2

f(1) = 3(1) - 4

f(1) = 3 - 4

f(1) = -1

f(10) = 3(10) - 4

f(10) = 30 - 4

f(10) = 26

f(-1) = 3(-1) - 4

f(-1) = -3 - 4

f(-1) = -7

*Answers are bolded.*

Hope this helps, thank you :) !!

User Mitzi
by
5.5k points